Caribbean Report 29-12-1995 - Richards, Ken (anchor); Niles, Bertram (correspondent); Potter, Philip (interviewee); Watty, William (interviewee); Thomas, Moya (correspondent); Jenkins, Stephen (interviewee); Coughlan, Geraldine (correspondent); Paul, Eric (interviewee); Orr, Carol (correspondent); Neutelings, Michel (interviewee); Roberts, Andy (interviewee); Crosskill, Hugh (correspondent) (The British Broadcasting Corporation, 1995)
In this report the late Governor General Dame Nita Barrow is laid to rest in her native Barbados. Dr. Philip Potter, former General Secretary of World Council of Churches and William Watty, President of the Caribbean Methodist Church paid tribute to Dame Nita and her significant achievements. Trinidad and Tobago's Prime Minister Basdeo Panday is set to undergo angioplasty surgery in London. Dr. Stephen Jenkins, Consultant Cardiologist will perform the operation and comments on the chances for success. In St. Martin, hotel workers left jobless by the passage of hurricane Luis continue protest action in spite of arrests and the use of teargas. The tiny island of Barbuda receives maximum attention from the British press as Princess Diana is there on vacation. In cricket, the West Indies cricket coach, Andy Roberts remains concern about the performance of the team despite their first win in the Australian tour. Roberts states that there are still a number of problems to be ironed out.
1. Headlines with Ken Richards (00:00-00:25)
2. Dame Nita Barrow is laid to rest in Barbados (00:26-03:50)
3. Trinidad and Tobago's Prime Minister to undergo angioplasty surgery in London (03:52-06:05)
4. Ex-hotel workers in St. Martin took to the streets again to protest lay-offs after hurricane Luis (06:06-08:48)
Keywords: Governors general -- Death -- Barbados; Women diplomats -- Barbados; Prime ministers -- Trinidad and Tobago; Heart -- Surgery; Trinidad and Tobago -- Politics and government; Demonstrations -- Saint Martin; Hotels -- Employees; Unemployment -- Saint Martin; Princesses -- Great Britain; Vacations -- Antigua and Barbuda; Cricket -- West Indies -- Management; Cricket coaches -- West Indies; Cricket -- Tournaments; Athletes -- Training of; Barrow, Nita, 1961-1995 -- Death and burial